ReStress mindset: An internet-delivered intervention that changes university students’ mindset about stress in the shadow of the COVID-19 pandemic - Karampas, Konstantinos; Pezirkianidis, Christos; Stalikas, Anastassios (Frontiers in Psychology, 2022)
The aim of this study is to evaluate “ReStress Mindset,” an internet-delivered intervention that combines the Stress Mindset Training Program (SMTP) with Acceptance and Commitment Therapy (ACT). To that end, the current study determined whether the pilot study’s findings on the intervention’s effectiveness on stress mindset and stress response among university students in the midst of the COVID-19 pandemic, remained for 3 months following the completion of “ReStress Mindset” intervention. Twenty-six participants were randomly assigned to an intervention (N = 12) and a control (N = 14) group. Participants in the intervention group attended 5 weekly sessions online, between the second and third waves of the COVID-19 pandemic. All participants completed self-report questionnaires (Stress Mindset Measure, Satisfaction With Life Scale, Depression Anxiety and Stress Scale-9, Perceived Stress Scale, Scale of Positive, and Negative Experience) before, at the end of the intervention and 3 months after the completion of the program. The “ReStress Mindset” intervention resulted in a statistically significant increase in “stress-is-enhancing” mindset (SIEM), life satisfaction, and self-efficacy against stress, as well as a statistically significant decrease in “stress-is-debilitating” mindset (SIDM), with these effects lasting 3 months after the program’s completion. The findings of this study suggest that university students could benefit from the “ReStress Mindset” intervention in order to cultivate and maintain a positive stress mindset and increase their life satisfaction and self-efficacy against stress, even during the COVID-19 pandemic or any other highly stressful period or crisis.